ANALISIS DAMPAK KEBERADAAN PT. CIPTA AGUNG MANIS (CAM) TERHADAP KONDISI SOSIAL EKONOMI DAN LINGKUNGAN MASYARAKAT SEKITAR DI KABUPATEN KONAWE SELATAN - Lia Prawita; Iskandar Zainuddin Rela; Salahuddin Salahuddin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
The purpose of this study was to analyze the impact of the existence of PT Cipta Agung Manis (CAM) on the socio-economic and environmental conditions of the surrounding community. The sample in this study was 24 people who were determined using the Snowball sampling technique. The data analysis used in this research is qualitative data analysis which consists of data reduction, data presentation, verification and drawing conclusions. The results of this study are that the existence of PT. CAM affected the socio-economic and environmental conditions of the nearest villages in Mataiwoi Village and Wunduwatu Village. Because the planting is done on privately owned land and production tasks are handled by PT CAM staff, the community does not participate in PT CAM operations. Social changes, such as in the field of education, namely the existence of PT CAM has had a good impact, such as increasing the income of villagers so that the environment is able to send the children of the local community to school. Economic factors that changed due to the presence of PT CAM in the village had a beneficial effect, as evidenced by changes in people's jobs due to the presence of PT CAM in the village. To reduce unemployment in Wunduwatu Village and Mataiwoi Village, PT.CAM influences the community's economy and creates employment opportunities for the community. In the Mataiwoi community and Wunduwatu Village, environmental changes caused by PT.CAM include air pollution which causes the community's air to smell bad.